Підсумки 60-річної діяльності насіннєвої лабораторії - Vakulenko, T.B.; Chuvikina, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The role of Seed Laboratory in the creation of the Botanical Gardens plant collections is shown. The results of 60 years work on seed exchange, creation of seed bank and the research of morphological features of plant fruits and seeds are summarized.